Management of ganciclovir resistance cytomegalovirus infection with CMV hyperimmune globulin and leflunomide in seven cardiothoracic transplant recipients and literature review. Issue 1 (5th October 2021) - Santhanakrishnan, Karthik; Yonan, Nizar; Iyer, Kapil; Callan, Paul; Al‐aloul, Mohamed; Venkateswaran, Rajamiyer
Abstract: Cytomegalovirus (CMV) disease caused by genetically resistant CMV poses a major challenge in solid organ transplant recipients, and the development of resistance is associated with increased morbidity and mortality. Antiviral resistance affects 5%–12% of patients following ganciclovir (GCV) therapy, but is more common in individuals with specific underlying risk factors. These include the CMV D+R‐ serostatus, type of transplanted organ, dose and duration of (Val)GCV ([V]GCV) prophylaxis, peak viral loads, and the intensity of immunosuppressive therapy. Guideline recommendations for the management of GCV resistance (GanR) in solid organ transplant recipients are based on expert opinion as there is a lack of data from controlled trials. Second‐line options to treat GanR include foscarnet (FOS) and cidofovir (CDV), but these drugs are often poorly tolerated due to high rates of toxicity, such as renal dysfunction and neutropenia. Here, we report seven cardiothoracic transplant recipients with GCV resistance CMV infection from our centre treated with CMV immunoglobulin (CMVIG) +/‐ leflunomide (LEF) and reviewed the literature on the use of these agents in this therapeutic setting.